2009
DOI: 10.1038/ja.2008.7
|View full text |Cite|
|
Sign up to set email alerts
|

Modification of the antibiotic olivomycin I at the 2′-keto group of the side chain. Novel derivatives, antitumor and topoisomerase I-poisoning activity

Abstract: A novel way of chemical modification of the antibiotic olivomycin I at the 2¢-keto group of the side chain of the aglycone moiety was developed. Reaction of olivomycin I with the carboxymethoxylamine hemihydrochloride gave the key intermediate, 2¢-carboxymethoxime-olivomycin I, which was further reacted with different amines in the presence of benzotriazol-1-yl-oxytrispyrrolidinophosphonium hexafluorophosphate to give the corresponding amides. The antiproliferative and topoisomerase I (Topo-I)-poisoning activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Studies by other researchers and us 7,14,20 have shown that the formation of complexes of chromomycin A 3 , mithramycin and 1 with DNA induced changes in CD spectra. Importantly, a correlation between the intensity of the induced CD spectra of drug-DNA complexes and the structure of the drug has been demonstrated.…”
Section: ' A4 E4mentioning
confidence: 93%
“…Studies by other researchers and us 7,14,20 have shown that the formation of complexes of chromomycin A 3 , mithramycin and 1 with DNA induced changes in CD spectra. Importantly, a correlation between the intensity of the induced CD spectra of drug-DNA complexes and the structure of the drug has been demonstrated.…”
Section: ' A4 E4mentioning
confidence: 93%
“…8) may even have potential usefulness as anti-hepatitis C virus agents. 193 In the mean time, novel derivatives of the antibiotic olivomycin 194,195 and novel anthracene-9,10-diones 196 were reported, although they were considered only as cytostatic, and, regretfully, not as (potential) antiviral agents.…”
Section: H Glycopeptide (And Other) Antibiotic Derivatives: An As Yementioning
confidence: 99%
“…Ïåðâîå íàïðàâëåíèå (ðèñ. 2, íàïðàâëåíèå 1) îñíîâàíî íà ïîëó÷åíèè îêñèìà ïî 2¢-êåòîãðóïïå áîêîâîé öåïè âçàèìîäåéñòâèåì îëèâîìèöèíà À ñ êàðáîêñèìåòîêñèëàìèíîì [78,79]. Ðåàêöèÿ ïðîòåêàåò ðåãèîñåëåêòèâíî ïî 2¢-êåòîãðóïïå áîêîâîé öåïè, ïðèâîäÿ ê êëþ÷åâîìó ñîåäèíåíèþ -2¢-êàðáîêñèìåòîêñèìîëèâîìèöèíó À. Äðóãîå èññëåäîâàííîå íàïðàâëåíèå ìîäèôèêàöèè (ðèñ.…”
unclassified